Pengaruh Karakteristik Ibu Terhadap Pemberian Asi Eksklusif - Harlianah Harlianah; Muhammad Sobri; Nura Malahayati (Jurnal Empirika, 2017)
Achievement of coverage of exclusive breastfeeding is one of the problems in Indonesia, both on the national and local levels. According to the Ministry of Health of the Republic of Indonesia achievement of exclusive breastfeeding in Indonesia at 80%. While the coverage of exclusive breastfeeding in Lahat regency still far below the national target. According to data from the Department of Health Lahat which saw a row of 37.15% (2009), 68.47% (2010), 36.58% (2011), 24.92% (2012) and 24.68% ( 2013). The study aimed to determine the prevalence of exclusive breastfeeding in the District Lahat, District and Sub-District West Merapi Gumay Ulu, and to identifies the influence of maternal characteristics on exclusive breastfeeding in the District Lahat, District and Sub-District West Merapi Gumay Ulu. The data used are primary data and interpretation of results using a logistic regression model approach. The study design was cross-sectional with a sample of 73 respondents mothers of children 6-12 months who come to Posyandu health centers in Region Research. Data were collected through interviews unified. Variables used include maternal age, maternal education, maternal employment status, maternal birth attendants, type of childbirth mother, IMD, mother's knowledge and mother attitude. The study's findings showed the prevalence of exclusive breastfeeding in the research area, District Lahat, District and Sub-District West Merapi Gumay Ulu respectively - helped by 36.2%, 58.3%, and 0%. Overall the proportion of mothers who exclusively breastfed for 38.4%. The results of logistic regression showed that the variables maternal age, maternal education, IMD, knowledge and attitudes of mothers are maternal characteristics that influence exclusive breastfeeding. From the research conducted, it was found that the most dominant variables potentially affecting exclusive breastfeeding is the IMD.